Sacculina nectocarcini, a new species of rhizocephalan (Cirripedia: Rhizocephala) parasitising the red rock crab Nectocarcinus integrifrons (Decapoda: Brachyura: Portunidae) - Gurney, Robert H.; Rybakov, Alexey V.; Høeg, Jens T.; Kuris, Armand M. (Zootaxa, 2006)
The parasitic barnacles, Rhizocephala, are a little known group within Australia with only seven described species from a coastline stretching approximately 59763 km. This study describes a new species of Rhizocephala, Sacculina nectocarcini. The description is based on a unique combination of features pertaining to the structure of the mantle papillae, the retinaculae and the male receptacles. Biological notes, prevalence and intensity of infection are reported for this rhizocephalan, infesting the red rock crab, Nectocarcinus integrifrons, collected from Western Port, Victoria, Australia.